Public sphere and private sphere – masculinity and femininity - Rosicki, Remigiusz (My University, 2012)
The text presents the analysis of categories such as public sphere, private sphere, masculinity, femininity. It is important to go beyond the physical understanding of sphere and focus on reflection on the social area. The sphere was recognized as a sphere of participation, i.e. as a special kind of interaction, presentations, and legitimacy of collective or individual identity. It is important for the analysis to indication that a particular discourse within science and in society, strengthen the interpretation of human life and specific practices. In this work, different mechanisms of sexism as the exclusion of women from the public sphere or assigning them to specific social roles in public or private life were considered. The text focuses on: (1) demographic description of population, (2) religious exclusion, (3) social practices within specific areas of activity. Patriarchal culture gave men a higher position in society, which resulted in a significant accumulation of the social, cultural, symbolic potential, etc. The dominance of men in many spheres such as politics, science, education, economy, combined with the exclusion of women, helped set up rules of activities and interpretation of social reality in accordance with the androcentric matrix. On the one hand, this could affect the very description and division of public and private area, on the other hand it laid certain social roles for women in public and private life.
The text presents an analysis of categories of public and private sphere, which are connected with the social division of roles based on gender. The sphere was recognized as a sphere of participation, i.e. as a special kind of interaction, presentation, and legitimacy of collective or individual identity. It is important for the analysis to indicate that a particular discourse, within science and in society, strengthen the interpretation of human life and specific practices. Consolidated in this way discourse facilitated the exclusion of women from public life, and, therefore, also reverse process, that means emancipation (subsequent waves of feminism). In the text three elements that could affect the consolidation of sexism were presented: (1) demographic descriptions of the population, (2) religious exclusion, (3) social practices within specific areas of activity. Demographic description of the human population, which can be found in the various fields or trends, such as environmentalism, sociobiology and bio-politics, affects quantitative interpretations. Qualitative elements were brought to the analysis of human reproductive functions, and the woman in the analysis had a definite role in society. However, the religious exclusion was only stressed on the example of Christianity. An analysis of exclusion in the case of religion may be considered on two levels – internal and social. In the first case we deal with the exclusion of women within the church structure itself, in the second case we deal with using the ideological content to shape the roles and functions of women in society. The last element contributing to the perpetuation of sexism are defined social practices described on the example of the concept of fields and capital of P. Bourdieu and the idea of economic, political and ideological domination of Karl Marx. It should be noted that the dominance of men in society influenced the possibility of significant accumulation of capital (e.g. social, cultural, symbolic). The presence of men in many spheres combined with the exclusion of women, helped to set up rules, practices and interpretations of social reality in accordance with an androcentric matrix. It affected to a large extent the assignment of women to certain social roles in public and private area.
Keywords: Femininity; Masculinity; Private sphere; Public sphere; Sphere of social practices; Field and habitus; Fields of male dominance; Private character; Public character; Political character; Gender